Sukuk Rating and Financial Ratio of Islamic Banks - Kurnia Agustina; Heni Noviarita; Erike Anggraini; Surono Surono (Journal of Islamic Economics Lariba, 2021)
The risk of default if the rating shows a decreasing result over several years of maturity measurement that can apply in banking institutions requires banking institutions to maintain or even increase the rating of sukuk issued. The purpose of this study is to discuss the effect of profitability ratios, liquidity ratios, leverage, and productivity ratios on the rankings of sukuk in Islamic banking institutions issuing sukuk. By using purposive sampling from 14 Islamic banks, 6 Islamic banking institutions were obtained as research samples in the 2015-2019 period, which were analyzed using multiple linear regression showing that only the productivity variable had a significant and positive influence on the rankings of sukuk in Islamic banking institutions, although with positive coefficient, profitability does not have a significant effect on the sukuk rating. Meanwhile, the liquidity and leverage variables did not have a significant effect and formed a negative relationship pattern on the sukuk rating in the Indonesian Islamic banking institutions issuing the sukuk. This concludes that only the productivity ratio can increase the rating of sukuk issued by banking institutions, while other ratios such as profitability do not have a significant effect and the financial ratios of liquidity and leverage will decrease the rating of the sukuk. So, this research suggests that in maximizing the rating of sukuk, the proxies for banking productivity should be increased.